Perencanaan Pembelajaran Musik Tradisi Di Kelas XII.4 SMA Kartika 1-5 Kota Padang - Anajmul Karim; Harisnal Hadi (FBS Universitas Negeri Padang, 2020)
This study aims to describe the instruction planning implemented in Class at XII.4 SMA Kartika 1-5 Padang City. Students’ high enthusiasm for music lessons and many achievements in the field of music are evidences that the teacher has succeeded in implementing learning strategies.This research used a descriptive qualitative method. The subjects of this research were music teachers, school principal, and some students of Class XII.4 at SMA Kartika 1-5 Padang City. The object of this research was learning strategies applied in SMA Kartika 1-5 Padang City.The data were collected through observation, interview, and documentation. The source triangulation technique was used to test the validity of the data. It was conducted by comparing one data source to another as materials for data analysis. Interactive analysis was used as technique to analyze the data. There are four components: 1) data collection technique 2) data reduction 3) data presentation and 4) conclusion making.Based on the results, it can be concluded that there are several strategies of music learning implemented in SMA Kartika 1-5 Padang City. The strategies are: 1) learning preparation; 2) learning management; 3) media use; 4) methods, models, and approaches implementation; 5) approaches to motivate students; 6) learning evaluation.